Pragmatic analysis of flexing through impression management in the television series Suits - Shelly Salammah; Mangatur Nababan; Agus Hari Wibowo (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
Flexing, commonly understood as showing off material possessions or achievements, has gained prominence in social interactions, particularly among youth. This study examines flexing from a pragmatic perspective, applying Goffman's Impression Management theory to analyze the linguistic strategies employed in the television series Suits. Using qualitative descriptive methods, the research identifies various impression management tactics such as ingratiation, intimidation, self-promotion, exemplification, and supplication as manifested in characters' dialogues. The findings reveal that flexing is a complex communicative strategy for constructing and negotiating social identity and status through language rather than merely superficial boasting. This linguistic approach enriches existing literature focusing on psychological and sociological aspects by highlighting language as a performative tool in social hierarchy reproduction. Moreover, the study discusses the educational implications of flexing behaviours in shaping student social dynamics and suggests pedagogical strategies for educators to foster healthier communication environments. Limitations include reliance on fictional media as data sources, warranting further empirical research in real educational contexts. This research contributes to the interdisciplinary understanding of communication, pragmatics, and education in the digital age.